(untitled) (BIRDEM Medical Journal, 2025)
Chikungunya is one of the fast-spreading viral infectious diseases of global concern. Initial clinical manifestations of chikungunya and dengue are similar and early identification of each may tailor the treatment strategy. Reverse-transcriptase polymerase chain reaction (RT-PCR) technology can identify these infections with high sensitivity and specificity. Ten cases of RT-PCR confirmed chikungunya were analyzed. Age of the patients ranged from 23 to 66 years and six were females. Three had diabetes mellitus and hypertension. Presentation included fever (100%), arthralgia/arthritis (90%), rash (50%) and post-auricular lymphadenopathy (20%). Total white cell counts and their differentials were variable. Most had high erythrocyte sedimentation rates and C-reactive protein levels. Initial treatment was paracetamol and other symptomatic remedies along with ongoing medications for comorbidities. None entered in subacute phase while writing this report. Along with early detection and treatment, preventive strategies should be strengthened to reduce the disease transmission. BIRDEM Med J 2025; 15(3): 136-140